Empowering girls and connecting people through school social work intervention programme (2014)
The girl-child is hindered from achieving her full potential in life due to an "unknown burden". The unknown unexpected burden comprises people, poverty, pregnancy, diseases, illiteracy and maltreatment. The purpose of the paper is to examine if the girl-child could be empowered to live an improved qualitative life through a school social work intervention and connecting the people who will support the girl-child. Are there problems in the life of a girl-child that prevent her from maximizing her educational opportunities? The intervention was conducted in two schools in Akinyele Local Government Area, Oyo State, Nigeria. All students (638) who attended the intervention workshop constituted the sample for the study. Data was collected through questionnaires administered after a presentation of the "unknown burden" of the girl-child to the entire school population. Data collected were analysed through frequency counts and percentages. Findings showed that the majority of the girls were aware of their burden, even though they do not know how to deal with it. In conclusion, the intervention was successful at giving the girl-child a forum to air her burden and help her to idem& sources of support. Recommendations made included the establishment of the position of school social workers and the empowerment of the girl-child to be self-determined to succeed at school.